2019
DOI: 10.1002/slct.201903649
|View full text |Cite
|
Sign up to set email alerts
|

Hot‐Injection Synthesis of PbE (E= S, Se) Nanoparticles from Dichalcogenoimidophosphinato Lead (II) Complexes

Abstract: Dichalcogenoimidodiphoshinato lead complexes, [Pb((EPiPr2)2N)2] (E=S, Se) have been synthesized and characterized. The crystal structure of [Pb((SeSPiPr2)2N)2]), has been solved by single‐crystal X‐ray crystallography and reported. These complexes have been used as single‐source precursors to synthesise PbS and PbSe nanoparticles by hot‐injection method in an oleylamine/trioctylphosphine mixture. Powder X‐ray diffraction (p‐XRD) studies indicate that the nanoparticles produced are cubic. The optical band gaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…e EDAX quantification on the thin films (Figure 6) indicated the formation of PbSe (52%:48%) at all the deposition temperatures. e thin films were lead rich, which is similar to our earlier reports [24,25,34,36,37].…”
Section: Sem Micrographs Of the In Filmssupporting
confidence: 91%
See 1 more Smart Citation
“…e EDAX quantification on the thin films (Figure 6) indicated the formation of PbSe (52%:48%) at all the deposition temperatures. e thin films were lead rich, which is similar to our earlier reports [24,25,34,36,37].…”
Section: Sem Micrographs Of the In Filmssupporting
confidence: 91%
“…Ternary lead sulphide selenide (PbS x Se 1−x ) nanocrystals and thin films [4,[18][19][20] have not been studied extensively relative to PbS and PbSe [21][22][23][24][25][26][27][28]. Nanocrystalline semiconductor alloys give an alternative route to quantum confinement effects and bandgap tuning and thus produce new materials with unique properties [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Lead sulfide semiconductor has a narrow gap [8,13,14], which makes it different from other semiconductors. e bandgap of PbS is affected by temperature and particle size [12,15]. e high sensitivity of the properties of PbS to particle size makes it well suited for nanostructured devices [12].…”
Section: Introductionmentioning
confidence: 99%
“…A search of the Cambridge Structural Database (CSD) showed that although imidodiphosphinate ligands with S 2 - and Se 2 -donor atom sets are well studied, there are comparatively a few reported structures of mixed Se/S donor imidodiphosphinate ligands. The bis­((diisopropylthiophosphoryl)­(diisopropylselenophosphoryl)­amido-S,Se) metal chelates are limited to Pb 2+ , Zn 2+ , Ni 2+ , Pt 2+ , Ga 3+ , and In 3+ . , The manganese­(II)-coordinated compound 2 is thus unique. Bis­(P,P,P′,P′-tetraisopropyldiselenoimidodiphosphinato) metal chelates with various divalent metal ions including, but not limited to, Ni 2+ , Hg 2+ , Pt 2+ , Cd 2+ , Sn 2+ , Pb 2+ , and Co 2+ have been reported; , the Mn 2+ chelate is, however, previously unknown.…”
Section: Resultsmentioning
confidence: 99%